Removal of failed dental implants revisited: Questions and answers. Issue 6 (21st August 2019) - Solderer, Alex; Al‐Jazrawi, Adrian; Sahrmann, Philipp; Jung, Ronald; Attin, Thomas; Schmidlin, Patrick R.
Abstract: Objectives: This narrative review is aiming on showing reasons for implant failure, removal techniques, and respective clinical considerations; further, the survival rate of implants in previous failed sites is examined. Materials and methods: Questions have been formulated, answered, and discussed through a literature search including studies assessing implant failure and removal up to 2018. Results: Studies describing reasons for implant failure, implant removal techniques, and the reinsertion of implants in a previous failed site ( n = 12) were included. To date, peri‐implantitis is the main reason for late implant failure (81.9%). Trephine burs seem to be the best‐known method for implant removal. Nevertheless, the counter‐torque‐ratchet‐technique, because of the low invasiveness, should be the first choice for the clinician. Regarding zirconia implant removal, only scarce data are available. Implantation in previously failed sites irrespective of an early or late failure results in 71% to 100% survival over 5 years. Conclusion: If removal is required, interventions should be based on considerations regarding minimally invasive access and management as well as predictable healing. (Post)Operative considerations should primarily depend on the defect type and the consecutive implantation plans.